Need for Telemedical Abortion Services in Indonesia and Malaysia: Study on Women on Web - Handayani, Amalia Puri; Gomperts, Rebecca (Yayasan Jurnal Perempuan, 2017)
The law restricting abortion in Indonesia and Malaysia doesn’t prevent any abortion, but instead, it forces women to take the health and life risk by using an unsaved abortion method. However, medical abortion in women’s residence by using mifepristone and misoprostol is very safe and effective, as mentioned in a research done by the WHO (2012). The research analyzes the figure of needs of Women on the Web service in 2015. Women on Web portal is visited by 355,004 visitors from Indonesia and 33,781 from Malaysia in 2015. As much as 1.989 women from Indonesia and 1.109 from Malaysia contacted the helpdesk of Women on Web. The figures show that there is a big need of information and access to safe medical abortion in Indonesia and Malaysia.